PENGARUH COMPATIBILTY LIFESTYLE MILENIAL DAN PERAN ENDORSER INFLUENCER TERHADAP MINAT BELI PADA PENGGUNA “TIKTOK” SHOP - Dinda Nimasayu Safri; Tri Sudarwanto (Universitas Muhammadiyah Gresik, 2022)
The purpose of this study was to analyze and examine the effect of millennial lifestyle compatibility and the role of influencer endorsers on buying interest on TikTok Shop. This study uses a descriptive type of research with a quantitative approach method, the sampling technique used in this research is using the lameshow formula with a total of 100 TikTok users aged 17-33 years and has shopped at the TikTok Shop. Collecting data using a questionnaire via google form. Statistical analysis in this study using SPSS with SPSS version 22 for Windows. The results of this study have a positive and significant effect. However, the results of the study show that the match between millennial lifestyles and buying interest has a greater direct influence than the influence of the endorser's role on buying interest. This research can help online stores or companies that have problems with some systems to do promotions. First of all, the researcher suggests online stores or TikTok to pay regular attention to the content produced by their users so that they can encourage endorser users to submit videos that are interesting and based on product benefits more clearly